Correlation between implementation of health protocol and compliance among employees of Mutiara department store Slawi in the prevention of Covid-19 - Pratiwi, Anggit; Subekti, Agung Tyas; Rakhmadi, Triyono (Universitas Ahmad Dahlan, 2022)
Background: Covid-19 pandemic has affected various aspects. One of them is the shopping center/retail sector since a shopping center is a place which is susceptible to the dissemination of SARS-CoV-2 viruses so that health protocols should be implemented and employees should comply with the health protocols in the workplace. Objective: The study is aimed at finding the correlation between the implementation of Covid-19 health protocols and compliance among employees of Mutiara Cahaya Department Store Slawi. Method: This is a quantitative correlative study with cross-sectional design. The research subjects were all employees of Mutiara Cahaya Department Store Slawi with the sample consisting of 48 respondents. Data Analysis: Data were analyzed using a univariate test in the form of frequency distribution and a bivariate test using Chi-Square. The results of the analysis showed that the implementation of Covid-19 health protocols in Mutiara Cahaya Department Store Ciawi ran quite well (39.59%) with employees’ compliance which was good as well (64.58%). The results of the research showed that there was a significant correlation between the implementation of health protocols and employees’ compliance with (pValue = 0,000) meaning that if the health protocol is good then the employees’ compliance is also good. Conclusion: Compliance with the implementation of health protocol which has been performed by the employees and management of Mutiara Cahaya Department Store Ciawi included mask wearing, hand washing, temperature check for employees and visitors, limitation of operational hours, provision of >1 meter distancing marks, installation of separators on cashier desks, and workplace cleaning with disinfectants.